1980
DOI: 10.1192/bjp.136.5.492
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual Respiratory Changes and Symptoms

Abstract: The duration of standardised overbreathing required to produce slow wave activity in the EEG during different phases of the menstrual cycle has been studied, and changes in carbon dioxide sensitivity of the respiratory system. Normal subjects developed slow waves more quickly and had more sensitive CO2 responses during the premenstrual/menstrual phases. This may be a factor contributing to premenstrual tension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(8 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…Some investigators have suggested that physiological functions fluctuate with the menstrual cycle [12, 13]. Little information is available concerning the impact of hormonal changes during the menstrual cycle on the ocular function in healthy women [4, 5, 6].…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators have suggested that physiological functions fluctuate with the menstrual cycle [12, 13]. Little information is available concerning the impact of hormonal changes during the menstrual cycle on the ocular function in healthy women [4, 5, 6].…”
Section: Discussionmentioning
confidence: 99%
“…They were told to close their eyes during the LIH procedure in order to minimize feelings of light-headedness and confusion. Because prior reports suggested increased sensitivity to hyperventilation at the menstrual and premenstrual phases of the cycle (Damas-Mora, Davies, Taylor, & Jenner, 1980), all premenopausal women were assessed during the ovulation phase, which was determined by asking subjects their cycle length and usual ovulatory onset.…”
Section: Methodsmentioning
confidence: 99%
“…Stressful circumstances may sensitize women to mild premenstrual changes that might otherwise go unnoticed or be tolerated with more equanimity (140,141). Stressful events also may affect physiologic processes that alter a woman's menstrual experience (for reviews, see 142,143).…”
Section: Psychiatric Historymentioning
confidence: 98%